The Prevalence of Acceptable Quality of Women Herbal Products Sold Online in Malaysia - Amir Omar, Nurul Arina; Sabran, Siti Fatimah (Journal of Sustainable Natural Resources, 2023)
The aim of this study is to determine the prevalence of quality herbal products sold online in Malaysia. The quality of herbal products focuses on two specific issues which are the legality of the labelling on herbal products and microbial contamination in herbal products.  Using keywords such as â€˜herbal productsâ€™, â€˜jamuâ€™, and â€˜women herbal productsâ€™, a total of 111 herbal products were selected to observe the labelling of herbal products from Malaysian online stores (Lazada, Shopee and iHerbs). 90.1% of the selected products are registered and fulfilled the labelling guidelines as required by National Pharmaceutical Registration Authority (NPRA). Among the 10 samples from the legally registered products, all of the products were contaminated with gram-negative bacteria with accepted number of colony forming unit (CFU